(untitled) (Scientific journal of the Fergana State University, 2023)
This article looks at pleonastic expressions from the perspective of modern linguistic pragmatics. Today, there is an acute problem in the speech practices of the modern language personality, where tautology and redundancy of the message stand out, which is related to the linguistic phenomenon of pleonasm, which is one of the most frequent, common and ambiguous linguistic phenomena. The article describes the phenomenon under study, which is traditionally regarded as a deviation from the norm and understood as "redundancy of expressive means in certain utterances, particularly in rhetorical speech..